Toward a greater understanding of the brain processes underlying handgrip and handgrip fatigue - King, Michael T C (MRC/UCT RU for Exercise and Sport Medicine, 2016)
Handgrip is a ubiquitous human movement that determines how we interact with our environment. It is involved in almost every aspect of daily life (e.g. opening a door, handling cutlery, using tools) and like all human movement, its application is limited by muscle fatigue. However, the supraspinal mechanisms of handgrip and handgrip fatigue are not fully understood despite the importance of this fundamental movement, numerous publications, and its presence as a longstanding research topic. This thesis investigates the brain mechanisms of handgrip and handgrip fatigue using fMRI. It begins with a review of the literature in Chapter one, which evaluates the theories and evidence for central control of handgrip and muscle fatigue as well as describing the rationale to perform the experiments in this thesis. The methodology and analyses are also reviewed to provide rationale for their use and to facilitate the interpretation of subsequent experimental results. In order to understand the supraspinal mechanisms of handgrip and handgrip fatigue it is logical to first understand the most fundamental grip type (power vs. precision) and pattern (static vs. dynamic) by which handgrip can be performed.